EFFICACY OF CHUNDAI VATRAL CHOORNAM A SIDDHA POLY HERBAL FORMULATION IN TREATING TENSION TYPE OF HEADACHE (TTH) -A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2019)
Siddha system is an ancient system of medicine which is popularly practised around south India particularly in Tamilnadu. Siddhars were considered as the pioneer of Siddha system, this system of medicine mainly encompasses for a healthy life for human beings. Among the broad spectrum of treatment aspects in Siddha system Siddhars classify the forms of internal medicines into 32 types which are all unique by its preparations. Choornam is one of the forms of internal medicine which can be used as single as well as poly herbal formulations. In this case report a poly-herbal formulation in Siddha system was used to treat tension type of headache (TTH). A 30 years old male patient visited out-patient department of Ayothidoss Pandither Hospital in National Institute of Siddha, Chennai. Patient reported with the complaints of episodic and chronic headache which is band like around the head, the intensity becomes mild to moderate, pain increased during working hours for past 2 years. Patient advised to follow the internal medicine Chundai vatral choornam it relives the TTH immediately when he got those symptoms.